Estimation of nitrogen and sulfur mineralization in soils amended with crop residues contributing to nitrogen and sulfur nutrition of crops in the North Central U.S. Issue 18 (11th October 2018) - Kaur, Jashandeep; Cihacek, Larry J.; Chatterjee, Amitava
ABSTRACT: Predicting nitrogen (N) and sulfur (S) mineralization of crop residues from the preceding crop might be a useful tool for forecasting soil N and S availability. Two soils from eastern North Dakota and three crop residues – corn, spring wheat, and soybean were used in an 8-week incubation study to estimate N and S mineralization from crop residues. The cumulative N and S mineralized were fit to a first-order kinetic model. Cumulative N mineralized ranged between 0.34 and 2.15 mg kg −1 and 0.45 to 3.41 mg kg −1 for the Glyndon and Fargo soils, respectively. Un-amended soils showed higher N mineralization than residue treated soils. For S, the highest mineralization occurred in un-amended Glyndon soil and in spring wheat-amended Fargo soil. This study indicates that crop residue additions can have a negative impact on plant available nutrients due to immobilization of N and S during the time when crops need the nutrients most.